Prevalence of Cadmium and Lead Residues in Fried Meat (Suya) Sold in Kaduna Metropolis, Kaduna State, Nigeria - Saulawa, M. A.; Jikamshi, M. A. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt